Airborne measurements of stratospheric constituents over Antarctica in the austral spring 1987. I - Method and ozone observations - Mankin, William G.; Coffey, M. T. (1989)
A Fourier transform spectrometer was flown aboard a DC-8 on 10 flights over Antarctica during August and September, 1987, as part of the Airborne Antarctic Ozone Experiment (AAOE). Observing the sun at infrared wavelengths, it was possible to determine the integrated column amount above the flight altitude for ozone and a number of other chemical species that are believed to be important in the perturbed chemistry of the 'ozone hole'. The paper describes the method, the observations, the data analysis procedure, and the ozone results. During the observation period, ozone developed a steep gradient near the edge of the polar vortex; deep within the vortex, the average ozone column decreased by about 1.6 percent per day during September.